Outdoor Learning: Changing The View Of The Boring Subject Of Pancasila Education In Elementary School - Naila Miftakhul Janah; Nur A'ini; Shelly Nur Yulianti; Deni Zein Tarsidi (Academic Solution Publisher, 2024)
Pancasila Education as a compulsory subject in elementary schools is often seen as boring learning due to monotonous and conventional teaching methods. This study aims to examine how the implementation of outdoor learning methods can be an effective solution in changing students' perceptions of Pancasila Education subjects. Using a systematic literature review method, this research analyzes various reference sources related to the implementation of outdoor learning in learning Pancasila Education at the elementary school level. The method in writing this article uses a case study method with data collection techniques, namely interviews, observations, and literature studies. The results showed that outdoor learning succeeded in changing the learning paradigm from theoretical to more dynamic and meaningful. This method allows students to observe, feel, and practice Pancasila values directly through real experiences in the surrounding environment. Some effective implementation strategies include contextualized material planning, outdoor deliberation simulation, project-based approach, and joint reflection. The implementation of outdoor learning is proven to increase students' interest in learning and understanding of Pancasila Education materials, as well as help internalize Pancasila values through meaningful hands-on activities.